2016
DOI: 10.1371/journal.pone.0161845
|View full text |Cite|
|
Sign up to set email alerts
|

Kinetic Modeling and Graphical Analysis of 18F-Fluoromethylcholine (FCho), 18F-Fluoroethyltyrosine (FET) and 18F-Fluorodeoxyglucose (FDG) PET for the Fiscrimination between High-Grade Glioma and Radiation Necrosis in Rats

Abstract: BackgroundDiscrimination between glioblastoma (GB) and radiation necrosis (RN) post-irradiation remains challenging but has a large impact on further treatment and prognosis. In this study, the uptake mechanisms of 18F-fluorodeoxyglucose (18F-FDG), 18F-fluoroethyltyrosine (18F-FET) and 18F-fluoromethylcholine (18F-FCho) positron emission tomography (PET) tracers were investigated in a F98 GB and RN rat model applying kinetic modeling (KM) and graphical analysis (GA) to clarify our previous results.MethodsDynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 33 publications
4
24
0
Order By: Relevance
“…Overall, the standard 1TCM provided the best results in terms of feasibility and robustness with an appropriate description of the tracer kinetics. This is in concordance with results reported in animal studies 24 . Additionally, correlation of K 1 with overall patient survival was visible in K 1 from both the 1TCM and 2TCM.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Overall, the standard 1TCM provided the best results in terms of feasibility and robustness with an appropriate description of the tracer kinetics. This is in concordance with results reported in animal studies 24 . Additionally, correlation of K 1 with overall patient survival was visible in K 1 from both the 1TCM and 2TCM.…”
Section: Discussionsupporting
confidence: 94%
“…There are only few reports on detailed compartment model analysis in 18 F-FET PET in patients, and the question, which model best describes the kinetics of tracer uptake, metabolism and washout is still unanswered 23 , 24 . However, voxelwise tracer kinetic analysis holds the promise of unraveling tumor sub-volumes of different metabolic activity, which is especially relevant in high-grade glioma due to their infiltrative and heterogeneous nature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly and thanks to collaboration with neurosurgeons, authors pointed out a significant correlation between 18 F-FCH uptake and not only the percentage of viable tumor but also inflammation and reactive gliosis quantified by the pathologist. Radiolabeled choline uptake in inflammation was previously reported [8,9], demonstrated in rat models [10,11] and might be responsible for a limited specificity of 18 F-FCH to differentiate viable tumor from post-radiation processes, including radionecrosis [12,13]. In this study, quantification of 18 F-FCH uptake revealed higher tracer uptake in the presence of tumor than in the absence of tumor, though with SUV overlap.…”
Section: Dear Editorsupporting
confidence: 55%
“…The specific injected activities for each cassette are shown in Table 5-1, with activities from each container normalised for differing injection doses. to acquired single-tracer data (used in previous experiment) and the literature (130,131) for manually delineated ROIs of brain tumour and cortical tissue. While only a single mouse was imaged, the large number of intra-subject voxels allows voxel-wise investigations to be performed.…”
Section: Quantifying Errormentioning
confidence: 99%